Sporadic E responds to the 2022 Tonga volcano eruptions recorded by the Meridian Project - YangYi Sun; Tao Yu; Jin Wang; Chi Long (Earth and Planetary Physics)
In this study, ionosonde observations over Fuke (19.5°N, 109.1°E), Wuhan (30.5°N, 114.4°E), and Mohe (53.5°N, 122.3°E) were analyzed to demonstrate the responses of the sporadic E () to the severe atmospheric disturbances caused by the Tonga volcanic eruptions on January 15, 2022. The most prominent signature was the disappearance of the layer after ~10:00 UT over Wuhan and Fuke, which was attributed to the vertical drift caused by the eruptions. The occurred intermittently after 13:00 UT following the arrival of the tropospheric Lamb wave. To examine the causal mechanism for the intermittence, we also included data of horizontal winds in the mesosphere and lower thermosphere region recorded by the meteor radars at Wuhan and Mohe in this study. The wind disturbances with periods of ~20 hours contributed to the formation of the layer in the nighttime on January 15.